Pengembangan Desain Sambungan Gading-Gading Kapal Tradisional Bagan Siapiapi Menggunakan Software Berbasis Elemen Hingga - Aksa, Reysca Admi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The traditional ships in Bagan Siapiapi, Riau province have been made in many decades. However, design of structural ships are still used a conventional method in process of manufacture, installation and selection of raw materials. The objective of this study is to find optimum design of Bagan Siapiapiâs traditional ship structural joints by improving the design. The simulation method was performed in this study. A computer Aided Design and Computer Aided Engineering finite element-based software were used for determining of optimum design of Bagan Siapiapiâs traditional ship structural joints. The design of ship material used the wood of Keruing and Meranti. Bolts or glue were used as fastener for ship structrual joints. The simulation model selected Bouyancy of 61840 Newton and specific gravity of 9.81 m/s2 for loads at ship structural joints. Based simulation, Keruing wood was better than Meranti wood for material of ship structural design. The result had obtained âSambungan Bibir Lurus Berkaitâ, which 4 pieces of bolts of 14 mm diameter for fastening as an optimum design. The maximum stress obtained 217.51 MPa at joint area, while minimum stress of 0.32896 MPa at the bolts. The maximum strain was obtained 0.0835 mm/mm in joint area and minimum strain of 1.64x10-6 mm/mm on the bolts. Total deformation was obtained 1.605 mm on joint area.Keywords: Design Improvement, Joint, Wood, Ship, Finite Element